Flow Cytometry Indicators in Mycosis Fungoides/Sezary Syndrome: Unveiling Silent Disease - Kariyawasan, C. C.; Balasuriya, B. L. T.; Ranatunga, S. A. C. D. (Disease and Health Research - New Insights Vol. 1, 2024)
Mycosis Fungoides (MF) is the most common type of cutaneous T-cell lymphoma, accounting for 50% of all cutaneous lymphomas. Sezary Syndrome (SS) and MF are closely related T-cell neoplasms that are considered separately based on clinical features and cell of origin. Despite their differences, both conditions can be challenging to diagnose, particularly in the absence of clinical symptoms. Flow cytometry plays a crucial role in the diagnosis of MF and SS, with a characteristic immunophenotypic expression that includes the lack of CD7 as a common feature in all stages of the disease. This diagnostic tool is invaluable in identifying the specific markers that differentiate these lymphomas from other T-cell disorders. In clinical practice, it is not uncommon to encounter patients who are asymptomatic yet exhibit a flow cytometric profile indicative of MF/SS. Such cases are rarely documented in the literature, highlighting the need for increased awareness and detailed analysis of these silent presentations. Persistent lymphocytosis, for example, can be an initial finding that warrants further investigation through flow cytometry. The immunophenotypic profile of MF/SS typically includes bright positivity for markers such as smCD3, CD4, CD2, TCR\(α\)\(β\) , and CD5, with dim positivity for CD8. Conversely, markers such as CD7, TCR\(γ\)\(δ\), CD25, and CD26 are usually negative. The CD4+/CD8+ ratio is often altered, reflecting the underlying pathophysiology of these lymphomas. Despite the absence of clinical symptoms, such as those required by the International Society of Cutaneous Lymphomas (ISCL) and the European Organization for Research and Treatment of Cancer (EORTC) for staging MF and SS, the presence of a typical immunophenotypic pattern on flow cytometry is significant. It underscores the importance of utilizing advanced diagnostic techniques to uncover and manage silent diseases effectively. By understanding the flow cytometry indicators and their implications in the context of MF/SS, clinicians can better identify and treat patients who might otherwise remain undiagnosed until the disease progresses to more advanced stages. This knowledge is critical for early intervention and improved patient outcomes in cutaneous T-cell lymphomas.